Actionable Science for Small Island Communities: Wind Velocity and Sea‐Level Rise Enhance Tidal Flooding on Little Cumberland Island, Georgia - C. Bertram; C. A. Brown; E. Herrera; S. Lewis; R. L. McLachlan (Community Science, 2025)
Abstract Small island communities are among the first and hardest impacted by sea‐level rise, though climate initiatives often focus on more heavily populated and economically productive coastal cities. Furthermore, most climate‐impact studies focus on regional scales that may be less applicable to small islands with locally unique morphodynamics. Little Cumberland Island, Georgia, located in southeastern USA, is one example of an often‐overlooked small island community. The island is minimally developed; a single dock and dirt roads connect ∼40 homes. Residents report that tidal flooding of low‐elevation roads has increased in frequency and magnitude over remembered history and is a primary concern for the longevity of island infrastructure. However, without site‐specific flooding predictions, they are unsure how or when to develop the roads. Through community science, this study (a) quantified the impact of wind velocity on tidal flooding, (b) predicted future flooding due to sea‐level rise, and (c) provided actionable results and advice to island residents. Superimposing predicted sea‐level rise onto observed tidal elevations suggests that the frequency of high‐tide flood events which inundate roads by at least 15 cm may nearly double by 2030 and nearly triple by 2040. We advise residents to develop flood‐resilient elevated roads within the next decade. This community‐driven project involved local knowledge, collective action, and social learning with external and internal expertise, though communal agreement on governance for resilient development would benefit from an alignment of conservation values and an extended period of time.